Krasava, a new genus of Pteromalidae (Hymenoptera, Chalcidoidea) from the Palaearctic region - Tselikh, Ekaterina V.; Rasplus, Jean Yves; Lee, Jaehyeon; Ku, Deok Seo (Zootaxa, 2025)
A new genus of Pteromalidae Krasava Tselikh, Rasplus & Lee, gen. nov., along with its type species Krasava sergeyi Tselikh, sp. nov., is described from the Republic of Korea. The genus can be distinguished by the following combination of characters: clypeus with neighbouring lateral parts convex, antenna inserted below ocular line, clava with a large micropilosity area on segments C1–C4, median area of propodeum concave, fore wing narrow.